Student perception toward factors contributing baby dumping issue: a case study of student bachelor administration science in UiTM Shah Alam / Muhammad Fikri Kassim and Mohamad Khairil Saidi - Kassim, Muhammad Fikri; Saidi, Mohamad Khairil (Faculty of Administrative Science and Policy Studies, 2013)
Recently in Malaysia, there are horrible phenomenon happened to a new epidemic in Malaysia and the government has started to look at it seriously. Baby dumping phenomenon is a phenomenon that we Malaysian should be embarrassed off. According to the Headquarters of Royal Malaysia Police (PDRM) baby dumping means that the acts of leaving away the babies at any places without taking care of the babies. The baby dumping issue arise when the woman had her unplanned pregnancy and been pressured by the question about the status of the child. Beside they may feel that they are not yet ready for his responsibility. In terms of “tradition”, young women fear rejection by their parents and the community if they are found to have had a baby outside of marriage. This tradition will absolutely increase the cases of baby dumping. Pregnant women that are rejected by their boyfriends, who may even deny being in any relationship with the woman and the child may then dump the baby because she fears that she will be unable to look after the child alone, or to afford the child’s maintenance. In conjunction prostitution also will cause baby dumping (Dianne Hubbard, Baby-dumping and Infanticide Report, 2008).